Transformation of Social Studies Education Based on Digital Citizenship in Shaping the Social Character of Generation Z in the Era of Society 5.0 - Ahmad Ramdan Pratama; Diah Lestari Prameswari; Fajar Mulki Santoso (Journal of Social Studies Education, 2026)
This study examines the transformation of Social Studies education based on digital citizenship in shaping the social character of Generation Z within the framework of Society 5.0. The research is motivated by the increasing influence of digital environments on students’ social behavior and the need for educational adaptation to support responsible civic development in the digital era. The study applies a quantitative explanatory design using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze the relationships between digital citizenship-based Social Studies education, Society 5.0 learning environments, and Generation Z’s social character. Data were collected from Generation Z students through structured questionnaires measuring digital citizenship competencies, perceptions of the learning environment, and social character indicators such as responsibility, tolerance, collaboration, and civic awareness. The results indicate that digital citizenship-based Social Studies education has a significant positive effect on students’ social character. In addition, the Society 5.0 learning environment strengthens this relationship by providing a human-centered digital ecosystem that supports interactive and value-based learning. The model demonstrates strong explanatory power, confirming that educational transformation plays a crucial role in shaping students’ civic and social behavior. The findings highlight that integrating digital citizenship into Social Studies education is essential for developing socially responsible and ethically aware learners. This integration enables students to navigate digital spaces more critically while maintaining strong social values. The study contributes to educational discourse by offering an integrated model of Social Studies transformation aligned with the demands of Society 5.0 and the characteristics of Generation Z.